Systematic review of diagnostic techniques for identification of pathogens in fresh milk from dairy herds with high bulk milk somatic cell count - Van Heerden, Henriette (University of Pretoria, 2022)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2021.